Energy of vacancy formation in the continuum matter model - Khrapak, A.G.; Khrapak, S.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
The quantum energy spectrum of the oscillating spherical void in solids is calculated within the continuummatter model. It is suggested that the ground state of the oscillating void corresponds to the vacancy in real crystals. The dependence of the vacancy formation energy on the shear modulus, density, pressure and surface tensionis determined. The obtained results are used to estimate properties of vacancies in solid Ar. A possibility touse the obtained results to estimate the properties of vacancies in liquid melts is discussed.